2007
DOI: 10.1523/jneurosci.2216-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Learning-Related Plasticity in PE1 and Other Mushroom Body-Extrinsic Neurons in the Honeybee Brain

Abstract: Extracellular recording were performed from mushroom body-extrinsic neurons while the animal was exposed to differential conditioning to two odors, the forward-paired conditioned stimulus (CSϩ; the odor that will be or has been paired with sucrose reward) and the unpaired CSϪ (the odor that will be or has been specifically unpaired with sucrose reward). A single neuron, the pedunculus-extrinsic neuron number 1 (PE1), was identified on the basis of its firing pattern, and other neurons were grouped together as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
132
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(141 citation statements)
references
References 47 publications
9
132
0
Order By: Relevance
“…Thus, even if key CS-processing stages such as the antennal lobes and the mushroom bodies have been studied in terms of their learning-dependent plasticity using olfactory conditioning of PER (see above and reviews in Menzel 1999; Giurfa 2007a), other CS processing sites such as the lateral horn remain unknown in terms of how odors are represented therein and whether learning induces functional and/or structural changes in this region. Downstream processing from olfactory receptors to mushroom bodies, including extrinsic mushroom body neurons (Mauelshagen 1993;Okada et al 2007;Strube-Bloss et al 2011), has been analyzed by means of different approaches that have been combined with PER conditioning. For instance, recent electrophysiological recordings have shown that mushroom body extrinsic neurons change their odor response spectra as a consequence of olfactory PER conditioning by losing or gaining sensitivity for specific odors (Strube-Bloss et al 2011).…”
Section: Cs Variationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, even if key CS-processing stages such as the antennal lobes and the mushroom bodies have been studied in terms of their learning-dependent plasticity using olfactory conditioning of PER (see above and reviews in Menzel 1999; Giurfa 2007a), other CS processing sites such as the lateral horn remain unknown in terms of how odors are represented therein and whether learning induces functional and/or structural changes in this region. Downstream processing from olfactory receptors to mushroom bodies, including extrinsic mushroom body neurons (Mauelshagen 1993;Okada et al 2007;Strube-Bloss et al 2011), has been analyzed by means of different approaches that have been combined with PER conditioning. For instance, recent electrophysiological recordings have shown that mushroom body extrinsic neurons change their odor response spectra as a consequence of olfactory PER conditioning by losing or gaining sensitivity for specific odors (Strube-Bloss et al 2011).…”
Section: Cs Variationsmentioning
confidence: 99%
“…The recording of Fifty years of PER conditioning in honeybees www.learnmem.org electromyograms of the muscles involved in proboscis extension, for instance, muscle M17 (Rehder 1987;Smith and Menzel 1989) or other muscles (Gauthier and Richard 1992), allowed a more graded measure of the animal's response. This technique can be efficiently used to measure a neural correlate of behavioral responses when movements of the proboscis should be prohibited, such as when coupled with other electrophysiological (Hammer 1993;Okada et al 2007;Denker et al 2010;Strube-Bloss et al 2011) or imaging recordings (Faber et al 1999;Hähnel and Menzel 2010). A few attempts have also been made using video recordings and subsequent analysis of PER parameters (Hosler and Smith 2000).…”
Section: Cs Variationsmentioning
confidence: 99%
“…For example, pharmacological inactivation of the MB during the differential conditioning trials was not impaired olfactory memory acquisition, suggesting that output region of MB do not involve in the olfactory differential conditioning (Devaud, Blunk, Podufall, Giurfa, & Grünewald, 2007). On the other hand, the 27 responses of α-lobe output neurons to sucrose associated odor clearly change during differential conditioning trials in honey bees (Mauelshagen, 1993;Okada, Rybak, Manz, & Menzel, 2007). Thus, the necessity of output region of Kenyon cells during olfactory conditioning in insects is still controversial.…”
Section: Neural Pathways Mediating Conditioned Olfactory Responses Ofmentioning
confidence: 99%
“…Appetitive associative learning can also be studied under controlled conditions in the laboratory by conditioning the proboscis extension response (PER) of individually harnessed honeybees 3,4 . This learning paradigm enables the study of the neuronal and molecular mechanisms that underlie learning and memory formation in a simple and highly reliable way [5][6][7][8][9][10][11][12] . A behavioral pharmacology approach is used to study molecular mechanisms.…”
mentioning
confidence: 99%